PARTISIPASI SISWA PEREMPUAN KELAS VII B DALAM MENGIKUTI MUATAN LOKAL KETRAMPILAN MEMBATIK DI SMP NEGERI 2 PEKALONGAN - -, Susanto (Solidarity: Journal of Education, Society and Culture, 2013)
Pekalongan famous for making batik Pekalongan dubbed as the city government tried to maintain the culture through education to students from an early age, through local content in schools. SMP N 2 local curriculum include batik in schools, the problem of this research is: How does the participation of female students of class VII B in following lessons batik skills and What are the factors driving and inhibiting factors VII B grade female students attend classes in batik skills. The research method used was a qualitative research method. Locations penelitianberada in SMP N 2. Subjects in this study were female students of class VII B. Informants pengampu supporting teacher research and curriculum wakasek SMP N 2 kota.Teknik data collection used was non-participatory observation, interviews and dokumentasi.Validitas data used is the technique of triangulation data. Data analysis techniques include four things: data collection, data reduction, data presentation, and conclusion.The results charge local batik in SMP N 2 still needs more participation from the students. Infrastructure Saranadan batik complete a driving factor of the participation of female students and the long process of making batik a factor of female students in learning local content batik.